GE_GERICHTE C/23868/2016 vom 2. November 2018 - GE Cour de justice (2018)
CONDITION DE RECEVABILITÉ;PRINCIPE DE LA BONNE FOI;FORMALISME EXCESSIF;DOMMAGE IRRÉPARABLE | CPC.319.leta; CPC.319.letb; CPC.52; CPC.132.al1; CPC.132.al3; CPC.225